Concurrent endurance and explosive type strength training improves neuromuscular and anaerobic characteristics in young distance runners - Mikkola, J.; Rusko, H.; Nummela, A.; Pollari, T.; Häkkinen, K. (International Journal of Sports Medicine, 2007)
To study effects of concurrent explosive strength and endurance training on aerobic and anaerobic performance and neuromuscular characteristics, 13 experimental (E) and 12 control (C) young (16 - 18 years) distance runners trained for eight weeks with the same total training volume but 19 % of the endurance training in E was replaced by explosive training. Maximal speed of maximal anaerobic running test and 30-m speed improved in E by 3.0 ± 2.0 % (p < 0.01) and by 1.1 ± 1.3 % (p < 0.05), respectively. Maximal speed of aerobic running test, maximal oxygen uptake and running economy remained unchanged in both groups. Concentric and isometric leg extension forces increased in E but not in C. E also improved (p < 0.05) force-time characteristics accompanied by increased (p < 0.05) rapid neural activation of the muscles. The thickness of quadriceps femoris increased in E by 3.9 ± 4.7 % (p < 0.01) and in C by 1.9 ± 2.0 % (p < 0.05). The concurrent explosive strength and endurance training improved anaerobic and selective neuromuscular performance characteristics in young distance runners without decreases in aerobic capacity, although almost 20 % of the total training volume was replaced by explosive strength training for eight weeks. The neuromuscular improvements could be explained primarily by neural adaptations.